2010
DOI: 10.1007/s12043-010-0046-3
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic star solutions in higher-dimensional pseudospheroidal space-time

Abstract: We obtain relativistic solutions of a class of compact stars in hydrostatic equilibrium in higher dimensions by assuming a pseudospheroidal geometry for the spacetime. The space-time geometry is assumed to be (D − 1) pseudospheroid immersed in a D-dimensional Euclidean space. The spheroidicity parameter (λ) plays an important role in determining the equation of state of the matter content and the maximum radius of such stars. It is found that the core density of compact objects is approximately proportional to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 25 publications
2
17
0
Order By: Relevance
“…However, in the literature there is some evidence available in favor of extra dimensions in compact stars [45][46][47][48][49][50].…”
Section: Resultsmentioning
confidence: 99%
“…However, in the literature there is some evidence available in favor of extra dimensions in compact stars [45][46][47][48][49][50].…”
Section: Resultsmentioning
confidence: 99%
“…Further, the red shift at the centre z c and on the boundary z R are both positive and finite. (2011); Chattopadhyay and Paul (2010); Chattopadhyay et al (2012). In this paper, we have obtained a new class of solutions to Einstein's field equations for a spherically symmetric anisotropic distribution of matter and have shown that our model can fit to the observational data of a number of well studied pulsars ( Gangopadhyay et al (2013)).…”
Section: Compact Star Modelsmentioning
confidence: 84%
“…);Tikekar (1999);Tikekar and Thomas (2005);Thomas et al (2005);Thomas and Ratanpal (2007);Paul et al (2011);Chattopadhyay and Paul (2010);Chattopadhyay et al (2012)). …”
mentioning
confidence: 99%
“…This spacetime, known as pseudo-spheroidal spacetime, has been studied by number of researchers Tikekar and Thomas (1998, 1999; Thomas et al (2005); Thomas and Ratanpal (2007);Paul et al (2011);Paul and Chattopadhyay (2010); Chattopadhyay and Paul (2012) have found that it can accommodate compact superdense stars.…”
Section: Spacetime Metricmentioning
confidence: 99%